The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1519/jsc.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

Lean Mass Asymmetry Influences Force and Power Asymmetry During Jumping in Collegiate Athletes

Abstract: The purpose of this investigation was to: (1) examine how asymmetry in lower extremity lean mass influenced force and power asymmetry during jumping, (2) determine how power and force asymmetry affected jump height, and (3) report normative values in collegiate athletes. Force and power were assessed from each limb using bilateral force plates during a countermovement jump in 167 Division 1 athletes (mass=85.7±20.3kg, age=20.0±1.2years, 103M/64F). Lean mass of the pelvis, thigh, and shank was assessed via dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
136
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 30 publications
12
136
2
2
Order By: Relevance
“…Between-group analyses also indicated a 'large' and significant difference between median-split fast and slow performers. Whilst previous investigations have associated asymmetries in force-related parameters with impaired athletic performance (Bailey et al, 2013;Bailey et al, 2015;Bazyler et al, 2014;Bell et al, 2014;Hart, Nimphius, et al, 2014), the relationship between asymmetry and CODS is not clear. Two investigations have noted reductions in CODS performance where an eccentric strength asymmetry is apparent (Chaouachi et al, 2012;Lockie et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Between-group analyses also indicated a 'large' and significant difference between median-split fast and slow performers. Whilst previous investigations have associated asymmetries in force-related parameters with impaired athletic performance (Bailey et al, 2013;Bailey et al, 2015;Bazyler et al, 2014;Bell et al, 2014;Hart, Nimphius, et al, 2014), the relationship between asymmetry and CODS is not clear. Two investigations have noted reductions in CODS performance where an eccentric strength asymmetry is apparent (Chaouachi et al, 2012;Lockie et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…It has since been observed that the expression of vertical stiffness and associated asymmetries is highly task dependant (Maloney, Fletcher, & Richards, 2015). As a change of direction may be characterised as acyclic, ballistic and unilateral in nature, the unilateral drop jump is likely to demonstrate the greatest correspondence to CODS and may therefore carry greater validity as an assessment for vertical stiffness Several investigations have reported that asymmetries in force/power qualities may be detrimental to athletic performance (Bailey, Sato, Alexander, Chiang, & Stone, 2013;Bailey, Sato, Burnett, & Stone, 2015;Bazyler, Bailey, Chiang, Sato, & Stone, 2014;Bell, Sanfilippo, Binkley, & Heiderscheit, 2014;Hart, Nimphius, Spiteri, & Newton, 2014), however, this relationship is not clear in regards to CODS. Whilst eccentric strength asymmetry has been linked to impaired CODS in some investigations (Chaouachi et al, 2012;Lockie, Shultz, Jeffriess, & Callaghan, 2012), Lockie et al (2014) reported that athletes with 'typical' asymmetries in unilateral jump performance (vertical jump: ∼10%; horizontal jump: ∼3%; lateral jump: ∼5%) did not experience speed detriments.…”
Section: Introductionmentioning
confidence: 99%
“…However, no attempt was made to quantify the association of MSA between unilateral tests. Hart et al [22] found lean mass asymmetry was related to reductions in kicking performance in Australian Football players, whereas Bell et al [7] found similar results showing a negative relationship between bilateral force and power asymmetry and unloaded CMJ performance. Moreover, recent studies have shown that carry-over of force production asymmetry exists in IMTP and CMJ [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of body asymmetry in athletes, the so-called symmetry index is used. This index has been used mainly to compare the symmetry between the right and left side of the body and between the upper and lower limbs, and in sports where body performance is determined by the use of the upper and lower limbs unilaterally and bilaterally [13][14][15][16]. The symmetry index is the most important parameter when evaluating functional asymmetries in athletes of different disciplines [17].…”
Section: Introductionmentioning
confidence: 99%